PLANT STOCK INFORMATION SYSTEM WITH REORDER POINT AND RBS (POLITEKNIK LP3I JAKARTA, 2026)
Unstructured inventory management can lead to recording errors, disorganized data, and difficulties in determining replenishment schedules and priorities. This issue occurred at CV. Sahabat Tani Berkah, where inventory management was still conducted manually. This study aimed to design and implement a web-based inventory management information system to support structured inventory recording, determine reorder timing, and prioritize stock replenishment. The system applied the Reorder Point (ROP) method to calculate reorder timing based on demand, lead time, and safety stock, while the Rule-Based System (RBS) method was used to determine replenishment priorities according to stock conditions and demand levels. The system was developed using the Waterfall methodology, consisting of analysis, design, implementation, and testing phases. Data were collected through observation and interviews, and the application was built using the Laravel framework. The results indicate that the system can manage incoming and outgoing inventory data in a structured manner, automatically calculate ROP and safety stock values, and classify replenishment priorities into high, medium, and low categories. Consequently, the system helps reduce the risks of stockouts and overstocking while improving the effectiveness of inventory management and replenishment decision-making.